Pengaruh Model Pembelajaran Learning Cycle Pada Mata Pelajaran Ilmu Pengetahuan Alam Terpadu Terhadap Aktivitas Belajar Siswa Di Sekolah Menengah Pertama Negeri 22 Kota Jambi - Indo Masse (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2019)
This study discusses the learning cycle of learning cycles in integrated Natural Sciences subjects towards student learning activities at SMP Negeri 22 Jambi City. This research is a quantitative study using a quasi-experimental design with a posttest only control design, while the data is carried out using a questionnaire. This study found that the use of the cycle learning model had a significant effect on student learning activities at SMP Negeri 22 Jambi City. From the data analysis using the